Islam, women's sexuality and patriarchy in Indonesia silent desire - Riyani, Irma. (London : Routledge, Taylor & Francis Group, 2021)
This book explores the intimate marital relationships of Indonesian Muslim married women. As well as describing and analysing their sexual relationships, the book also investigates how Islam influences discourses of sexuality in Indonesia, and in particular how Islamic teachings affect Muslim married women's perceptions and behaviour in their sexual relationships with their husbands. Based on extensive original research, the book reveals that Muslim women perceive marriage as a social, cultural, and religious obligation that they need to fulfil; that they realise that finding an ideal marriage partner is complicated, with some having the opportunity for a long courtship and others barely knowing their partner prior to marriage; and that there is a strong tendency, with some exceptions, for women to consider a sexual relationship in marriage as their duty and their husband's right. Religious and cultural discourses justify and support this view and consider refusal a sin (dosa) or taboo (pamali). Both discourses emphasise obedience towards husbands in marriage.
OCLC-licensed vendor bibliographic record.
Keywords: Married women -- Sexual behavior -- Indonesia; Wives -- Religious life -- Indonesia; Muslim women -- Sexual behavior -- Indonesia; Sex -- Religious aspects -- Islam; Patriarchy -- Indonesia; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research